Comparative study on the oblique water-entry of high-speed projectile based on rigid-body and elastic-plastic body model - Xiangyan Liu; Xiaowei Cai; Zhengui Huang; Yu Hou; Jian Qin; Zhihua Chen (Defence Technology)
To examine the similarities and differences in the evolution of cavity, wetting and dynamics of a high-speed, oblique water-entry projectile with different positive angles of attack, a comparative analysis has been conducted based on the numerical results of two mathematical models, the rigid-body model and fluid-structure interaction model. In addition, the applicable scope of the above two methods, and the structural response characteristics of the projectile have also been investigated. Our results demonstrate that: (1) The impact loads and angular motion of the projectile of the rigid-body method are more likely to exhibit periodic variations due to the periodic tail slap, its range of positive angles of attack is about α < 2°. (2) When the projectile undergone significant wetting, a strong coupling effect is observed among wetting, structural deformation, and projectile motion. With the applied projectile shape, it is observed that, when the projectile bends, the final wetting position is that of Part B (cylinder of body). With the occurrence of this phenomenon, the projectile ballistics become completely unstable. (3) The force exerted on the lower surface of the projectile induced by wetting is the primary reason of the destabilization of the projectile trajectory and structural deformation failure. Bending deformation is most likely to appear at the junction of Part C (cone of body) and Part D (tail). The safe angles of attack of the projectile stability are found to be about α ≤ 2°.